Charge Transfer within the F4TCNQ‐MoS2 van der Waals Interface: Toward Electrical Properties Tuning and Gas Sensing Application. (25th October 2018) - Wang, Jiawei; Ji, Zhuoyu; Yang, Guanhua; Chuai, Xichen; Liu, Fengjing; Zhou, Zheng; Lu, Congyan; Wei, Wei; Shi, Xuewen; Niu, Jiebin; Wang, Liang; Wang, Hong; et al.
Abstract: The development of van der Waals heterostructures in 2D materials systems has attracted considerable interests for exploring new insights of (opto‐) electrical characteristics, device physics, and novel functional applications. Utilizing organic molecular material with strong electron withdrawing ability, charge transfer van der Waals interfaces are formed between 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane (F4 TCNQ) and MoS2, via which the modulation of the onset voltages and optimization of subthreshold swing values in MoS2 ‐based field effect transistors are realized. Charge transfer process and its functionality mechanisms are further verified and investigated with first‐principles calculation, scanning Kelvin probe microscope characterization, and temperature‐dependent electrical characterization. With the charge transfer effect between reducing gas molecules and F4 TCNQ, NH3 gas sensor is proposed and fabricated with the sensitivity reaching higher than 1000% at 100 ppm, much more outstanding performance than those of any reported MoS2 ‐based NH3 gas sensors. The F4 TCNQ‐MoS2 hybrid strategy might open up a pathway for tuning and optimizing the electrical properties, in addition to novel functional units designing and fabrications in electric devices based on low‐dimensional semiconducting systems. Abstract : Employing the organic charge transfer material 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane, the electrical properties of MoS2 field‐effect transistors including V on 's and subthreshold swings are successfully modulated with no degradation of mobility. The charge transfer mechanism is investigated by first‐principles calculation and scanning Kelvin probe microscopy. A high‐performance NH3 gas sensor fabricated from this transistor reaches more than 1000% sensitivity at 100 ppm.